Canakinumab for the treatment of autoinflammatory very early onset- inflammatory bowel disease - Shaul, Eliana; Conrad, Máire A.; Dawany, Noor; Patel, Trusha; Canavan, Megan C.; Baccarella, Alyssa; Weinbrom, Sarah; Aleynick, Daniel; Sullivan, Kathleen E.; Kelsen, Judith R. (Frontiers in Immunology, 2022)
Introduction: Therapeutic options are critically needed for children with refractory very early onset inflammatory bowel disease (VEO-IBD). Our aim was to evaluate clinical response to canakinumab, an anti-IL-1β monoclonal antibody, in patients with VEO-IBD whose phenotype resembles those with monogenic autoinflammatory disease. Methods: This is a single center retrospective study of patients with VEO-IBD with autoinflammatory phenotype (AIP) in the absence of identified monogenic disease treated with canakinumab for >6 months. AIP was defined as confirmed IBD with associated signs of systemic inflammation in the absence of infection, including leukocytosis, markedly elevated inflammatory markers, and extraintestinal manifestations (recurrent fevers, oral ulcers, arthritis). Primary outcomes included clinical response in disease activity indices after 6 months of therapy. Secondary outcomes included rate of AIP signs and symptoms, growth, surgery, steroid use, hospitalizations, and adverse events. Results: Nineteen patients were included: 47% with infantile onset, 58% classified as IBD-U, and 42% classified as CD. At baseline, 37% were biologic naïve, and canakinumab was used as dual therapy in 74% of patients. Clinical response was achieved in 89% with statistically significant improvement in PCDAI and PUCAI. Clinical remission was achieved in 32% of patients. There was significant improvement in the clinical manifestations of AIP and the biochemical markers of disease. Number of hospitalizations (p<0.01) and length of stay (p<0.05) decreased. Growth improved with median weight-for-length Z-score increasing from -1.01 to 1.1 in children less than 2 years old. There were minimal adverse events identified during the study period. Conclusion: Canakinumab may be an effective and safe treatment for a subset of children with VEO-IBD with AIP, as well as older patients with IBD. This study highlights the importance of a precision medicine approach in children with VEO-IBD.